1995
DOI: 10.1007/bf01839249
|View full text |Cite
|
Sign up to set email alerts
|

Pathological studies in broiler chicks fed aflatoxin or ochratoxin and inoculated with inclusion body hepatitis virus singly and in concurrence

Abstract: Day-old broiler chicks found negative for maternal antibodies against inclusion body hepatitis (IBH) virus by agar gel precipitation test and viral antigen in cloacal swabs by dot enzyme immunoassay were divided into 6 groups of 20 chicks each. Group A was fed aflatoxin B1 at 1.25 ppm from 3 to 38 days of age; group O was fed ochratoxin A at 0.5 ppm from 3 to 38 days of age; group V was inoculated with 1 ml of IBH virus of titre log10 6.5 EID50 per 0.2 ml. Groups AV and OV were given aflatoxin B1 and ochratoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 20 publications
4
14
0
Order By: Relevance
“…The changes in the liver and kidneys of broiler chicks fed OA in the present study are similar to those reported by Huff et al (1974Huff et al ( , 1975, Prior et al (1976), Dwivedi & Burns (1984a), Mohiuddin et al (1992) and Sandhu et al (1995). Gross and histopathological changes in the liver and kidneys recorded following S. Gallinarum infection were also similar to those reported by Chishti et al (1985), Kaushik et al (1986), Sandhu et al (1987), Kokosharov et al (1997), and Deshmukh et al (2005) in the liver and/or kidney of birds affected naturally or experimentally with S. Gallinarum.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The changes in the liver and kidneys of broiler chicks fed OA in the present study are similar to those reported by Huff et al (1974Huff et al ( , 1975, Prior et al (1976), Dwivedi & Burns (1984a), Mohiuddin et al (1992) and Sandhu et al (1995). Gross and histopathological changes in the liver and kidneys recorded following S. Gallinarum infection were also similar to those reported by Chishti et al (1985), Kaushik et al (1986), Sandhu et al (1987), Kokosharov et al (1997), and Deshmukh et al (2005) in the liver and/or kidney of birds affected naturally or experimentally with S. Gallinarum.…”
Section: Discussionsupporting
confidence: 82%
“…OA may increase the severity and/or frequency of secondary infections in birds (Elissalde et al, 1994;Sandhu et al, 1995;Fukata et al, 1996;Koynarski et al, 2007). Elissalde et al (1994) fed 3 parts/10 6 OA to broiler chickens and inoculated them with Salmonella Typhimurium.…”
Section: Introductionmentioning
confidence: 99%
“…The severity of these lesions in both organs in the combination group was more than those in either group, suggesting an additive effect of OA and E. coli. Sandhu et al (1995) also reported that pathological changes in liver and kidneys of chicks receiving OA and IBH virus were more severe than the chicks given OA or IBH virus alone.…”
Section: Discussionmentioning
confidence: 91%
“…Dwivedi and Burns [47] noticed enzymatic inhibition of glycogenolysis in ochratoxin toxicosis and this could be due to excess glycogen observed in the kidney of rat. According to Sandhu et al [48], the treatment of chicks with OA led to increase in mucopolysaccharides (MPS) in liver and kidney tissues. Increase in glycogen content was noticed after treatment with ginseng and OA at different durations in comparison with OA alone.…”
Section: Discussionmentioning
confidence: 99%